Cloning genes for the biosynthesis of a macrolide antibiotic. - Fishman, S E (1987)
Macrocin-O-methyltransferase (MacOMeTase) catalyzes the final enzymatic step in the biosynthesis of tylosin in Streptomyces fradiae. A 44-base mixed oligonucleotide probe containing only guanosine and cytidine in the third position of degenerate codons was synthesized based on the amino acid sequence of the amino terminus of MacOMeTase. Plaque blot hybridization to a bacteriophage lambda library and colony blot hybridization to a cosmid library of S. fradiae DNA identified recombinants that contained overlapping fragments of chromosomal DNA. The nucleotide sequence of the cloned DNA verified that the DNA contained the coding sequence for MacOMeTase. Recombinant plasmids transformed mutants blocked in tylosin biosynthesis and complemented tylF (the structural gene for MacOMeTase) and tyl mutations of eight other classes.